2016
DOI: 10.1111/eje.12242
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and attitudes of dental students in regard to child abuse in Turkey

Abstract: Dental students in Turkey are not sufficiently prepared for their role in diagnosing suspected cases of child abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 25 publications
5
41
2
6
Order By: Relevance
“…Cukovic-Bagic et al (2015) found dental practitioners’ knowledge of CAN to be limited and that, concomitantly, there were high levels of uncertainty and hesitation among practitioners when diagnosing and reporting suspected cases. Several studies found, like Cukovic-Bagic et al (2015), that this could lead to misattribution errors in diagnosis and/or result in inconsistent documentation of potential signs of abuse and neglect (da Fonseca et al, 1992; Hazar Bodrumlu, Avsar & Arslan, 2018; Kvist, Annerback & Dahllof, 2018; Preethi, Einstein & Sivapathasundharam, 2011). Similar findings were made by Deshpande et al (2015), Hussein, Ahmad, Ibrahim, Yusoff and Ahmad (2016), Kaur et al (2016), Malpani et al (2017), Mogaddam, Kamal, Merdad and Alamoudi (2016), Al-Jundi, Zawaideh and Al-Rawi (2010), Sonbol et al (2012), Thomas, Straffon and Inglehart (2006), Tilvawala, Murray, Farah and Broadbent (2014), and Uldum, Christensen, Welbury and Poulsen (2010).…”
Section: Resultsmentioning
confidence: 99%
“…Cukovic-Bagic et al (2015) found dental practitioners’ knowledge of CAN to be limited and that, concomitantly, there were high levels of uncertainty and hesitation among practitioners when diagnosing and reporting suspected cases. Several studies found, like Cukovic-Bagic et al (2015), that this could lead to misattribution errors in diagnosis and/or result in inconsistent documentation of potential signs of abuse and neglect (da Fonseca et al, 1992; Hazar Bodrumlu, Avsar & Arslan, 2018; Kvist, Annerback & Dahllof, 2018; Preethi, Einstein & Sivapathasundharam, 2011). Similar findings were made by Deshpande et al (2015), Hussein, Ahmad, Ibrahim, Yusoff and Ahmad (2016), Kaur et al (2016), Malpani et al (2017), Mogaddam, Kamal, Merdad and Alamoudi (2016), Al-Jundi, Zawaideh and Al-Rawi (2010), Sonbol et al (2012), Thomas, Straffon and Inglehart (2006), Tilvawala, Murray, Farah and Broadbent (2014), and Uldum, Christensen, Welbury and Poulsen (2010).…”
Section: Resultsmentioning
confidence: 99%
“…Tabela 3. Distribuição da proporção percentual de acertos dos alunos do 8º e 10º para as perguntas a respeito do conhecimento geral e diagnóstico de violência contra crianças e adolescentes 17 , em um estudo realizado com estudantes da Turquia, observaram que apenas 22,14% dos alunos entrevistados observaram esta associação.…”
Section: Sexo ( ) M ( ) Funclassified
“…A maioria dos estudantes entrevistados associaram a violência aos estratos socioeconômicos mais baixos, resultados também observados por Jundi et al (2017) 20 em pesquisa com estudantes de pós-graduação em duas escolas de Odontologia da Jordânia. O estudo realizado por Bodrumlu et al (2018) 17 observou que 25,26% dos alunos estavam cientes de que o abuso infantil pode ocorrer entre pessoas de alta renda.…”
Section: Sexo ( ) M ( ) Funclassified
“…Diş hekimleri ve personeller, yalnızca kendi başına bir endişe olarak değil, aynı zamanda genel bir ihmal uyarısı olabileceği için, dental ihmalin belirtilerini iyi bilmelidirler 45 . Bodrumlu ve ark 46 . On Dokuz Mayıs Üniversitesi Diş Hekimliği öğrencilerine çocuk istismarı ve farkındalığı hakkında yaptıkları anket sonuçları Türkiye'de diş hekimliği öğrencilerinin, şüpheli vakalarda çocuk istismarı teşhisi konusundaki rolleri için yeterli şekilde hazırlanamadığını ortaya koymaktadır.…”
Section: Dental İhmalden Kimler Sorumlu Olabilir?unclassified